Polymer, negative pole piece, battery and electric device
By modifying side-link branches of carboxymethylcellulose salts, reducing hydrogen bonding forces, improving the flexibility and dispersion of polymers, the problem of easy cracking of the battery electrode sheet is solved, and the flexibility of the negative electrode film layer is improved and Interface performance.
Patent Information
- Application Number
- CN202310732501.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
During the preparation of battery electrode plates, the electrode plates are prone to cracking, resulting in the performance not meeting production needs. Especially in the case of high-speed coating and thick coating, the flexibility and interface performance of the electrode plates are insufficient.
Modified carboxymethyl cellulose salt polymers are used to graft modification of the side chains of carboxymethyl cellulose salts, reducing hydrogen bonding forces, improving the flexibility and dispersion of the polymer, and used in the negative electrode film. The layer is used as a dispersant to reduce drying stress and improve flexibility.
It effectively reduces the risk of cracking of the negative electrode film layer, improves its flexibility and interface performance, makes the negative electrode active material evenly disperse, and improves the overall performance of the battery electrode sheet.
Smart Images

Figure CN119161585A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a polymer, a negative electrode sheet, a battery and an electrical device. Background Art
[0002] Battery cells are widely used because of their reliable working performance, no pollution, and no memory effect. For example, as environmental protection issues are increasingly valued and new energy vehicles become more popular, the demand for power battery cells will show explosive growth.
[0003] As the application range of batteries becomes wider and wider, the requirements for battery performance are becoming increasingly stringent. However, the current strong demand for high-speed coating and thick coating has resulted in the risk of cracking of the pole piece during the preparation process, resulting in the pole piece performance being unable to meet production requirements. Summary of the invention
[0004] The present application provides a polymer, a negative electrode plate, a battery and an electrical device. The performance of the battery plate described in the present application can be improved.
[0005] In a first aspect, the present application proposes a polymer, which includes a modified carboxymethyl cellulose salt, wherein the hydrogen atom of at least one hydroxyl group in the carboxymethyl cellulose salt is substituted with a grafted group, and the grafted group includes at least one of a polyether group and a substituted or unsubstituted polyalkyl group.
[0006] The polymer of the embodiment of the present application can be regarded as a modified carboxymethyl cellulose salt, that is, a polymer obtained by grafting the side chain of carboxymethyl cellulose salt (CMC-M), and the grafted group replaces the hydrogen atom in the hydroxyl group by grafting the side chain of the carboxymethyl cellulose salt, destroying the hydroxyl structure in the carboxymethyl cellulose salt, thereby destroying the regular hydrogen bond structure and reducing the number of hydrogen bonds; the group replacing the hydrogen atom in the hydroxyl group includes a polyether group, a polyalkyl group, etc., which is basically unable to form a hydrogen bond, thereby reducing the force between the polymer molecular chains, increasing the free volume of the polymer network, and promoting the relative movement between the polymer molecular chains, thereby reducing the stress generated during drying, and improving the flexibility of the negative electrode film layer, reducing the risk of cracking of the negative electrode film layer, and improving the interface performance of the negative electrode film layer. Moreover, since the main structure of the polymer is still a carboxymethyl cellulose salt, it still has a good dispersing effect, which can effectively reduce the interfacial tension between the negative electrode active material and the solvent, so that the negative electrode active material is evenly dispersed in the negative electrode slurry.
[0007] In some embodiments, the modified carboxymethyl cellulose salts include at least one of modified carboxymethyl cellulose lithium salt, modified carboxymethyl cellulose sodium salt, or modified carboxymethyl cellulose ammonium salt. The above materials have good dispersibility.
[0008] In some embodiments, the modified carboxymethyl cellulose salts include repeating units represented by formula (A),
[0009]
[0010] In formula (A), M includes at least one of Li, Na or NH4;
[0011] R1 to R5 each independently include at least one of hydrogen atoms, C5 to C150 polyether groups, substituted or unsubstituted C5 to C150 saturated alkyl groups, substituted or unsubstituted C5 to C150 polyalkenyl groups, and at least one of R1 to R5 includes at least one of C5 to C150 polyether groups, substituted or unsubstituted C5 to C150 saturated alkyl groups, substituted or unsubstituted C5 to C150 polyalkenyl groups, wherein the grafted group includes non-hydrogen atom groups in R1 to R5; n represents the degree of polymerization of the modified carboxymethyl cellulose salt; optionally, n includes any positive integer from 1500 to 3000. The above material has good dispersibility and weak hydrogen bonding, and because the grafted group has a relatively long chain segment, the hydrogen bonding effect can be further weakened, thereby improving the flexibility of the polymer applied to the negative electrode film layer.
[0012] In some embodiments, the grafted group includes a polyether group, and the polyether group includes the structural formula shown in formula (1),
[0013]
[0014] In formula (1), R 11 To R 17 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, a substituted or unsubstituted C1 to C10 alkenyl group, and a substituted or unsubstituted C1 to C10 alkynyl group;
[0015] m includes any positive integer from 5 to 60.
[0016] In the embodiment of the present application, a part of the hydroxyl groups in the polymer are unsubstituted, and another part of the hydroxyl groups in the polymer are substituted by long-chain polyether groups. Since the polyether groups occupy a relatively long space, they have a steric hindrance effect and can weaken the hydrogen bonding effect formed by the unsubstituted hydroxyl groups, thereby reducing the interaction force between the polymer molecular chains, further reducing the drying stress, and improving the interface performance of the negative electrode film layer.
[0017] In some embodiments, the grafted group includes at least one of the structural formulas shown in formula (1-1) to formula (1-14),
[0018]
[0019]
[0020] In some embodiments, the grafted group includes a substituted or unsubstituted first group, wherein the substituted or unsubstituted first group includes the structural formula shown in formula (2),
[0021]
[0022] In formula (2), R 21 To R 27 Each independently includes at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group;
[0023] s includes any positive integer from 5 to 60.
[0024] Therefore, a part of the hydroxyl groups in the polymer of the embodiment of the present application are unsubstituted, and another part of the hydroxyl groups in the polymer are substituted by long-chain saturated alkyl groups. Since the saturated alkyl groups occupy a longer space, they have a steric hindrance effect and can weaken the hydrogen bonding effect formed by the unsubstituted hydroxyl groups, thereby reducing the interaction force between the polymer molecular chains, further reducing the drying stress, and improving the interface performance of the negative electrode film layer.
[0025] In some embodiments, the grafted group includes at least one of the structural formulas shown in formula (2-1) to (2-10),
[0026]
[0027] In some embodiments, the grafted group includes a substituted or unsubstituted second group, wherein the substituted or unsubstituted second group includes the structural formula shown in formula (3),
[0028]
[0029] In formula (3), R 31 To R 34 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, and a substituted or unsubstituted C1 to C10 alkenyl group;
[0030] R 35 including at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group;
[0031] p includes any positive integer from 5 to 60.
[0032] Therefore, a part of the hydroxyl groups in the polymer of the embodiment of the present application are unsubstituted, and another part of the hydroxyl groups in the polymer are substituted by long-chain polyalkenyl groups. Since the polyalkenyl groups occupy a longer space, they have a steric hindrance effect and can weaken the hydrogen bonding effect formed by the unsubstituted hydroxyl groups, thereby reducing the interaction force between the polymer molecular chains, further reducing the drying stress, and improving the interface performance of the negative electrode film layer.
[0033] In some embodiments, the grafted group includes at least one of the structural formulas shown in formula (3-1) to formula (3-8),
[0034]
[0035] In some embodiments, the weight average molecular weight of R1 to R5 is 100 Da to 5000 Da. The molecular weight of the grafted group in the polymer is relatively small, which can reduce the hydrogen bonding effect between the polymer molecular chains and make the polymer have better dispersibility.
[0036] In some embodiments, the weight average molecular weight of the polymer is 40 wDa to 80 wDa; when the weight average molecular weight of the polymer is within the above range, the polymer can have excellent dispersibility.
[0037] In some embodiments, the elongation at break of the reference film made of sodium carboxymethyl cellulose is 100%, the elongation at break of the film made of the polymer is 170% to 300%, and the width of the reference film and the film made of the polymer is 2.5 cm, the length is 5 cm, and the thickness is 1 mm.
[0038] Therefore, the elongation at break of the polymer in the embodiment of the present application is higher than that of conventional sodium carboxymethyl cellulose. When the polymer is applied to the negative electrode plate, it has better flexibility and is not prone to breakage.
[0039] In a second aspect, the present application further proposes a dispersant, which includes a polymer as described in any embodiment of the first aspect of the present application. The dispersant can be used in the negative electrode film layer of the negative electrode plate to improve the thickness uniformity and flexibility of the negative electrode film layer.
[0040] In some embodiments, the dispersant may also include carboxymethyl cellulose salts.
[0041] In some embodiments, the ratio of the mass content of the carboxymethyl cellulose salt to the mass content of the polymer can be 0.5 to 2. When the mass content ratio of the carboxymethyl cellulose salt to the polymer is within the above range, it can work together with the polymer to improve the flexibility of the film formed by itself.
[0042] In a third aspect, the present application further proposes a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a polymer as described in any embodiment of the first aspect of the present application.
[0043] In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the polymer is 1.0% to 1.3%, and optionally 1.0% to 1.2%. When the mass content of the polymer is within the above range, the flexibility of the negative electrode film layer can be effectively improved, and the negative electrode active material in the negative electrode film layer is more evenly dispersed, and the performance of the negative electrode film layer is more uniform.
[0044] In some embodiments, the coating weight of the negative electrode film layer is 190 mg / 1540.25 mm 2 Up to 230mg / 1540.25mm 2 ; Optional: 200mg / 1540.25mm 2 Up to 230mg / 1540.25mm 2 The coating weight of the negative electrode film layer is relatively high, which is conducive to achieving thick coating.
[0045] In a fourth aspect, the present application also provides a battery, the battery comprising the negative electrode sheet as described in any embodiment of the third aspect of the present application. The battery comprises a battery cell / battery module and a battery pack.
[0046] In a fifth aspect, an embodiment of the present application further proposes an electrical device, comprising a battery as described in any embodiment of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0048] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0049] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.
[0050] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0051] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0052] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0053] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0054] The drawings are not necessarily drawn to scale.
[0055] The following are the descriptions of the reference numerals:
[0056] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0057] 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate;
[0058] 6. Electrical equipment. DETAILED DESCRIPTION
[0059] Hereinafter, the embodiments of the polymer, negative electrode plate, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0060] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0061] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0062] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0063] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0064] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0065] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0066] The term "polyether group" refers to a group formed by polymerization of ether-containing monomers. For example, the polyether group can be a C5-C500 polyether group, a C20-C400 polyether group, a C1-C50 polyether group, a C1-C40 polyether group, a C1-C30 polyether group, a C1-C20 polyether group, a C1-C12 polyether group, a C1-C10 polyether group, a C1-C6 polyether group, or a C1-C4 polyether group. In addition, the polyether group can be optionally substituted.
[0067] The term "saturated alkyl" encompasses straight and branched saturated alkyl groups. For example, the saturated alkyl group may be a C5-C500 saturated alkyl group, a C20-C400 saturated alkyl group, a C1-C50 saturated alkyl group, a C1-C40 saturated alkyl group, a C1-C30 saturated alkyl group, a C1-C20 saturated alkyl group, a C1-C12 saturated alkyl group, a C1-C10 saturated alkyl group, a C1-C6 saturated alkyl group, a C1-C4 saturated alkyl group. In addition, the saturated alkyl group may be optionally substituted. The term "halogenated saturated alkyl group" refers to a saturated alkyl group in which a hydrogen atom is partially or completely replaced by a halogen atom, and the term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.
[0068] The term "polyalkenyl" encompasses straight and branched polyalkenyls. For example, polyalkenyl can be C5-C500 polyalkenyl, C20-C400 polyalkenyl, C2-C50 polyalkenyl, C2-C40 polyalkenyl, C2-C30 polyalkenyl, C2-C20 polyalkenyl, C2-C12 polyalkenyl, C2-C10 polyalkenyl, C2-C6 polyalkenyl, C2-C6 polyalkenyl, C2-C4 polyalkenyl. In certain embodiments, polyalkenyl includes second polyalkenyl, third polyalkenyl, fourth polyalkenyl, fourth polyalkenyl, fifth polyalkenyl, sixth polyalkenyl, heptyl polyalkenyl, octyl polyalkenyl etc. In addition, polyalkenyl can be optionally substituted.
[0069] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D) or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0070] In various places of this specification, the substituent of compound is disclosed in groups or scopes.It is clearly expected that this description includes each individual subcombination of the members of these groups and scopes.For example, it is clearly expected that the term "C1-C8 alkyl" discloses C1, C2, C3, C4, C5, C6, C7, C8, C1-C8, C1-C7, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C8, C2-C7, C2-C6, C2-C5, C2-C4, C2-C3, C3-C8, C3-C7, C3-C6, C3-C5, C3-C4, C4-C8, C4-C7, C4-C6, C4-C5, C5-C8, C5-C7, C5-C6, C6-C8, C6-C7 and C7-C8 alkyl individually.
[0071] As other examples, the integers in the range of 5-40 are specifically intended to disclose individually 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40; the integers in the range of 1-20 are specifically intended to disclose individually 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. Accordingly, other groups or ranges are specifically contemplated.
[0072] When the above groups are substituted, the substituents may be independently selected from halogen atoms or heteroatoms.
[0073] As used herein, the term "polymer" refers to a molecular complex consisting of more than ten monomer units and generally includes, but is not limited to, homopolymers, copolymers, such as block, graft, random and alternating copolymers, terpolymers, and higher order "x" polymers, further including their analogs, derivatives, combinations and mixtures. In addition, unless otherwise specifically limited, the term "polymer" shall include all possible isomeric configurations of the molecule, including but not limited to isotactic, syndiotactic and random symmetry and combinations thereof. In addition, unless otherwise specifically limited, the term "polymer" shall include all possible geometric configurations of the molecule.
[0074] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector. The negative electrode film layer is formed by coating the negative electrode slurry on the negative electrode current collector and drying. In the process of forming the negative electrode film layer by the negative electrode slurry, cracking and other phenomena may occur, resulting in the negative electrode sheet not meeting the production requirements. In order to improve the cracking phenomenon of the negative electrode film layer, the related technology adds plasticizers such as butanediol to the negative electrode slurry. The plasticizer is usually a small molecule compound (whose molecular weight is relatively small). The plasticizer can enter between the molecular chains of the binder polymer, reduce the intermolecular stress of the binder polymer, and reduce the crystallinity of the polymer molecular chain, thereby improving the shaping ability and flexibility of the negative electrode film layer and improving the cracking phenomenon of the negative electrode film layer. However, the residual plasticizer easily leads to uneven thickness of the negative electrode film layer, resulting in dark marks, metal precipitation and other interface problems in the negative electrode film layer.
[0075] In view of the above problems, the embodiment of the present application proposes a polymer, which can be used as a dispersant in the negative electrode film layer. The polymer includes modified carboxymethyl cellulose salts, that is, the carboxymethyl cellulose salts are grafted and modified so that the polymer has good flexibility. When applied to the negative electrode slurry, it can disperse the negative electrode active material, etc., and can thicken the negative electrode slurry, thereby improving the flexibility of the negative electrode film layer and improving the cracking phenomenon of the negative electrode film layer.
[0076] polymer
[0077] In a first aspect, an embodiment of the present application proposes a polymer comprising a modified carboxymethyl cellulose salt, wherein the modified carboxymethyl cellulose salt is a carboxymethyl cellulose salt in which at least one hydrogen atom of a hydroxyl group is substituted with a grafted group, wherein the grafted group comprises at least one of a polyether group and a substituted or unsubstituted polyalkyl group.
[0078] Carboxymethyl cellulose salts (CMC-M) are a type of anionic water-soluble cellulose ether derivatives. When used in negative electrode slurry, they can reduce the interfacial tension between the negative electrode active material and the solvent, and have a good dispersing effect on the negative electrode active material. Under stirring, it is beneficial for the negative electrode active material to be evenly dispersed in the solvent to form a stable slurry system.
[0079] The molecular chains of carboxymethyl cellulose salts are rich in hydroxyl groups (-OH). The presence of hydroxyl groups enables the molecular chains of carboxymethyl cellulose salts to form strong van der Waals forces or hydrogen bonds. In addition, carboxymethyl cellulose salts may be able to form strong van der Waals forces or hydrogen bonds with negative electrode active materials, etc., so that the negative electrode slurry has strong drying stress during the drying process and warps, and may crack during further rolling, causing cracking of the negative electrode film layer.
[0080] The polymer of the embodiment of the present application can be regarded as a modified carboxymethyl cellulose salt, that is, a polymer obtained by grafting the side chain of carboxymethyl cellulose salt (CMC-M), and the repeating unit included in the polymer can be one or more. By grafting the side chain of carboxymethyl cellulose salt, the grafted group replaces the hydrogen atom in the hydroxyl group, destroys the hydroxyl structure in the carboxymethyl cellulose salt, thereby destroying the regular hydrogen bond structure and reducing the number of hydrogen bonds; and the group replacing the hydrogen atom in the hydroxyl group includes a polyether group, a polyalkyl group, etc., which is basically unable to form a hydrogen bond, thereby reducing the force between the polymer molecular chains, increasing the free volume of the polymer network, and promoting the relative movement between the polymer molecular chains, thereby reducing the stress generated during drying, and improving the flexibility of the negative electrode film layer, reducing the risk of cracking of the negative electrode film layer, and improving the interface performance of the negative electrode film layer. Moreover, since the main structure of the polymer is still a carboxymethyl cellulose salt, it still has a good dispersing effect, which can effectively reduce the interfacial tension between the negative electrode active material and the solvent, so that the negative electrode active material is evenly dispersed in the negative electrode slurry, so that the thickness of the negative electrode film layer is evenly distributed. Therefore, the polymer can be applied to the negative electrode slurry (or the negative electrode film layer of the negative electrode sheet) as a dispersant.
[0081] In some embodiments, the modified carboxymethyl cellulose salts include at least one of modified carboxymethyl cellulose lithium salt, modified carboxymethyl cellulose sodium salt, or modified carboxymethyl cellulose ammonium salt. The above materials have good dispersibility.
[0082] In other embodiments, the modified carboxymethyl cellulose salts may also include modified carboxymethyl cellulose potassium salt and the like.
[0083] In some embodiments, the modified carboxymethyl cellulose salts include a compound represented by formula (A),
[0084]
[0085] In formula (A), M includes at least one of Li, Na or NH4;
[0086] R1 to R5 each independently include at least one of a hydrogen atom, a C5 to C150 polyether group, a substituted or unsubstituted C5 to C150 saturated alkyl group, and a substituted or unsubstituted C5 to C150 polyalkenyl group, and at least one of R1 to R5 includes at least one of a C5 to C150 polyether group, a substituted or unsubstituted C5 to C150 saturated alkyl group, and a substituted or unsubstituted C5 to C150 polyalkenyl group, wherein the grafted group includes a non-hydrogen atom group among R1 to R5; n represents the degree of polymerization of the modified carboxymethyl cellulose salt.
[0087] The above-mentioned material has good dispersibility and weak hydrogen bonding, and because the grafted group has a relatively long chain segment, the hydrogen bonding effect can be further weakened, thereby improving the flexibility of the polymer used in the negative electrode film layer.
[0088] Optionally, n includes any positive integer from 1500 to 3000. Exemplarily, n may be 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900 or 3000.
[0089] The non-hydrogen atom group means a non-hydrogen atom group, that is, when R1 to R5 all replace the hydrogen atoms in the hydroxyl group, R1 to R5 can be considered as grafted groups; if one of R1 to R5, for example R1, is a hydrogen atom, then R1 is not a grafted group.
[0090] The repeating unit in the modified carboxymethyl cellulose salts may include one or more, and the polymer may include one or more modified carboxymethyl cellulose salts.
[0091] It should be noted that at least one of R1 to R5 includes at least one of a polyether group, a substituted or unsubstituted polyalkyl group, which can be understood as a hydrogen atom in at least one hydroxyl group in the polymer being replaced, that is, at least one of R1 to R5 is not a hydrogen atom, for example, four of R1 to R5 are hydrogen atoms, or three of them are hydrogen atoms, or two of them are hydrogen atoms, and one of them is a hydrogen atom, or even R1 to R5 may not be hydrogen atoms. As the number of hydrogen atoms decreases, it means that the number of substituted hydroxyls in the polymer increases. The more substituted hydroxyls there are, the smaller the force between the polymer molecular chains, the smaller the drying stress of the negative electrode slurry, the less likely the negative electrode film layer is to crack, and its interface performance is improved. In the case where R1 to R5 are not hydrogen atoms, the polymer basically does not contain hydroxyls, the number of hydrogen bonds contained in the polymer is small, the action between the polymer molecular chains is small, the drying stress is significantly reduced, the negative electrode film layer is not likely to crack, and its interface performance is improved.
[0092] In order to further reduce the effect of hydrogen bonding in the polymer, it is considered to select the substituent group as a long chain structure, such as a C20-C100 long chain structure. Specifically, R1 to R5 each independently include at least one of a C20-C100 polyether group, a substituted or unsubstituted C20-C100 saturated alkyl group, and a substituted or unsubstituted C20-C100 polyalkenyl group. A portion of the hydroxyl groups in the polymer are unsubstituted, and another portion of the hydroxyl groups in the polymer are replaced by a long chain structure. The long chain structure has a steric hindrance due to its long space occupation, which can weaken the hydrogen bonding effect formed by the unsubstituted hydroxyl groups, thereby reducing the interaction between the polymer molecular chains, further reducing the drying stress, and improving the interface performance of the negative electrode film layer, so that the polymer has good flexibility and dispersibility when used as a negative electrode slurry. The substituent group may further be selected as a C20-C80 long chain structure. Specifically, R1 to R5 each independently include at least one of a C20-C80 polyether group, a substituted or unsubstituted C20-C80 saturated alkyl group, and a substituted or unsubstituted C20-C80 polyalkenyl group.
[0093] In some embodiments, R1 to R5 each independently include a polyether group, and the polyether group includes the structural formula shown in formula (1),
[0094]
[0095] In formula (1), R 11 To R 17 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, a substituted or unsubstituted C1 to C10 alkenyl group, and a substituted or unsubstituted C1 to C10 alkynyl group.
[0096] Optionally, when the above-mentioned groups are substituted, the substituent may include a halogen atom, wherein the halogen atom may include at least one of a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0097] m includes any positive integer from 5 to 60. Optionally, m includes any positive integer from 5 to 45. When m is within the above range, it can reduce the hydrogen bonding effect of the polymer while still having a good dispersion effect.
[0098] In some embodiments, m can be 5, 6, 7, 8, 9, 10, 12, 13, 14, 15, 16, 18, 20, 25, 30, 35, 40, 45, 50, 55, or 60.
[0099] Exemplarily, R1 to R5 each independently include at least one of the structural formulas shown in formula (1-1) to formula (1-14),
[0100]
[0101]
[0102] In some embodiments, m1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30.
[0103] In the embodiments of the present application, m-m1 represents the value of m minus m1, and m-m1 represents 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.
[0104] In some embodiments, the substituted or unsubstituted polyalkyl group includes at least one of a substituted or unsubstituted saturated alkyl group and a substituted or unsubstituted polyalkylene group. In this article, the saturated alkyl group can be defined as a first group; the polyalkylene group can be defined as a second group. That is, the substituted or unsubstituted polyalkyl group includes at least one of a substituted or unsubstituted first group and a substituted or unsubstituted second group.
[0105] In some embodiments, R1 to R5 each independently include a substituted or unsubstituted saturated alkyl group, and the substituted or unsubstituted saturated alkyl group includes the structural formula represented by formula (2),
[0106]
[0107] In formula (2), R 21 To R 27 Each independently includes at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 saturated alkyl group.
[0108] Optionally, when the above-mentioned groups are substituted, the substituent may include a halogen atom, wherein the halogen atom may include at least one of a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0109] s includes any positive integer from 5 to 60. Optionally, s includes any positive integer from 5 to 45. When s is within the above range, it can reduce the hydrogen bonding effect of the polymer while still having a good dispersion effect.
[0110] In some embodiments, s can be 5, 6, 7, 8, 9, 10, 12, 13, 14, 15, 16, 18, 20, 25, 30, 35, 40, 45, 50, 55, or 60.
[0111] Exemplarily, R1 to R5 each independently include at least one of the structural formulas shown in formula (2-1) to formula (2-10),
[0112]
[0113] In some embodiments, s1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30.
[0114] In the embodiments of the present application, s-s1 represents the value of s minus s1, and s-s1 represents 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.
[0115] In some embodiments, R1 to R5 each independently include a substituted or unsubstituted polyalkenyl group, and the substituted or unsubstituted polyalkenyl group includes the structural formula represented by formula (3),
[0116]
[0117] In formula (3),
[0118] R 31 To R 34 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, and a substituted or unsubstituted C1 to C10 alkenyl group;
[0119] R 35 The present invention includes at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group.
[0120] Optionally, when the above-mentioned groups are substituted, the substituent may include a halogen atom, wherein the halogen atom may include at least one of a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0121] p includes any positive integer from 5 to 60. Optionally, p includes any positive integer from 5 to 45. When p is within the above range, it can reduce the hydrogen bonding effect of the polymer while still having good dispersibility.
[0122] In some embodiments, p can be 5, 6, 7, 8, 9, 10, 12, 13, 14, 15, 16, 18, 20, 25, 30, 35, 40, 45, 50, 55, or 60.
[0123] Exemplarily, R1 to R5 each independently include at least one of the structural formulas shown in formula (3-1) to formula (3-8),
[0124]
[0125] In each of the above embodiments, the halogen atom may include at least one of a fluorine atom, a chlorine atom, and a bromine atom. The above atoms can improve the withstand voltage of the polymer.
[0126] In the above embodiments, the weight average molecular weight of R1 to R5 is 100Da to 5000Da. The molecular weight of the grafted groups in the polymer is relatively small, which can reduce the hydrogen bonding between polymer molecular chains and make the polymer have better dispersibility.
[0127] For example, the weight average molecular weight of R1 to R5 can be 100Da, 120Da, 150Da, 200Da, 250Da, 300Da, 350Da, 400Da, 450Da, 500Da, 550Da, 600Da, 650Da, 700Da, 750Da, 800Da, 850Da, 900Da, 950Da, 1000Da, 1050Da, 1100Da, 1150Da, 1200Da, 1250Da, 1300Da, 1350Da, 1400Da, 1450Da, 1500Da, 1550Da, 1600Da, 1650Da, 1700Da, 1750Da, 1800Da, 1850Da. 4700 Da, 4800 Da, 4900 Da, 5000 Da, 5100 Da, 5200 Da, 5300 Da, 5400 Da, 5500 Da, 5600 Da, 5700 Da, 5800 Da, 5900 Da, 6000 Da, 6100 Da, 6200 Da, 6300 Da, 6400 Da, 6500 Da, 6600 Da, 6700 Da, 6800 Da, 6900 Da, 7000 Da, 7100 Da, 7200 Da, 7300 Da, 7400 Da, 7500 Da, 7600 Da, 7700 Da, 7800 Da, 7900 Da, 8000 Da, 8100 Da, 8200 Da, 8300 Da, 8400 Da,
[0128] In some embodiments, the weight average molecular weight of the polymer is 40 wDa to 80 wDa. When the weight average molecular weight of the polymer is within the above range, the polymer can have excellent dispersibility.
[0129] Illustratively, the weight average molecular weight of the polymer can be 40wDa, 42wDa, 45wDa, 46wDa, 48wDa, 50wDa, 52wDa, 55wDa, 58wDa, 60wDa, 62wDa, 65wDa, 68wDa, 70wDa, 72wDa, 75wDa, 78wDa, 80wDa, or a range consisting of any two of the above values.
[0130] In the present application, the weight average molecular weight of the polymer can be tested by methods known in the art, such as gel chromatography, such as Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141).
[0131] Conventional sodium carboxymethyl cellulose is a solid polymer at room temperature. Sodium carboxymethyl cellulose is dissolved in solvent water with a mass content of 1%. After stirring at 1200 rpm for 2 hours, it is dried in an oven at, for example, 40°C for more than 24 hours to obtain a reference film with a width of 2.5 cm, a length of 5 cm, and a thickness of 1 mm. The elongation at break of the reference film is tested, and the elongation at break of the reference film is defined as 100%. It should be noted that conventional sodium carboxymethyl cellulose refers to sodium carboxymethyl cellulose whose side chains are not substituted by other groups, especially the hydrogen atoms at the hydroxyl position are not substituted.
[0132] In some embodiments, the polymer is prepared into a film, the polymer is dissolved in solvent water, the mass content of the polymer is 1%, and the film is dried in an oven, for example, at 40° C. for more than 24 hours after being stirred at 1200 rpm for 2 hours, to obtain a film with a width of 2.5 cm, a length of 5 cm, and a thickness of 1 mm; the elongation at break of the film is calculated by testing the elongation at break of the reference film as 100%, and the elongation at break of the film is 170% to 300%. When preparing the film, the thickness deviation of the film can be controlled within a range of 0.5%.
[0133] Therefore, the elongation at break of the polymer is higher than that of conventional sodium carboxymethyl cellulose. When the polymer is applied to the negative electrode plate, it has better flexibility and is not prone to breakage.
[0134] Illustratively, the elongation at break of the film may be 170%, 180%, 190%, 200%, 210%, 220%, 230%, 240%, 250%, 260%, 270%, 280%, 290%, 300% or a range consisting of any two of the above values.
[0135] In the present application, the elongation at break of the film has a well-known meaning in the art and can be tested using equipment and methods known in the art. Specifically, the test can be performed with reference to the standard GB / T36363-2018.
[0136] Method for preparing polymers
[0137] In a second aspect, an embodiment of the present application proposes a method for preparing a polymer, the method comprising step S100 of alkalization treatment and step S200 of substitution treatment.
[0138] In step S100, the alkalization treatment specifically includes: providing carboxymethyl cellulose salts, and subjecting the carboxymethyl cellulose salts to alkalization treatment with alkali to activate the hydroxyl sites of the carboxymethyl cellulose salts to form active reaction sites.
[0139] Carboxymethyl cellulose salts include compounds represented by formula (B),
[0140]
[0141] In formula (B), M includes at least one of Li, Na or NH4.
[0142] After the carboxymethyl cellulose salt is alkalized, the hydrogen atoms at the hydroxyl positions are activated. For example, sodium hydroxide NaOH or potassium hydroxide KOH is used for alkalization, and the hydrogen atoms at at least one hydroxyl position in the carboxymethyl cellulose salt are replaced by sodium Na atoms. For example, the hydrogen atoms at all hydroxyl positions of the carboxymethyl cellulose salt are replaced by Na. The intermediate product after the replacement is a compound shown in formula (C).
[0143]
[0144] In step S200, the substitution treatment specifically includes: adding a substitution compound into the system to carry out a substitution reaction. The substitution compound will replace the sodium Na atom at the hydroxyl position, and the product after substitution is a polymer, and the polymer is shown in the above formula (A).
[0145] The substituted compound includes at least one of polyethers, substituted or unsubstituted saturated alkanes, and substituted or unsubstituted polyolefins.
[0146] In some embodiments, the substituted compound includes polyethers, and the polyethers include compounds represented by formula (11),
[0147]
[0148] In formula (11), R 11 To R 17Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, a substituted or unsubstituted C1 to C10 alkenyl group, and a substituted or unsubstituted C1 to C10 alkynyl group.
[0149] m includes any positive integer from 5 to 60.
[0150] In some embodiments, the substituted compound includes a substituted or unsubstituted saturated alkane, and the substituted or unsubstituted saturated alkane includes a compound represented by formula (21),
[0151]
[0152] In formula (21), R 21 To R 27 Each independently includes at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group;
[0153] s includes any positive integer from 5 to 60.
[0154] In some embodiments, the substituted compound includes a substituted or unsubstituted polyolefin, wherein the substituted or unsubstituted polyolefin includes a compound represented by formula (31),
[0155]
[0156] In formula (31),
[0157] R 31 To R 34 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, and a substituted or unsubstituted C1 to C10 alkenyl group;
[0158] R 35 including at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group;
[0159] p includes any positive integer from 5 to 60.
[0160] In the preparation of the polymer, the reaction can be carried out under the reaction conditions commonly used in the art, and the molar ratio of each raw material can also be selected according to the molar ratio commonly used in the art.
[0161] Dispersants
[0162] In a third aspect, the present application provides a dispersant, which includes a polymer as described in any embodiment of the first aspect of the present application or a polymer obtained by the preparation method described in any embodiment of the second aspect of the present application. The dispersant can be used in the negative electrode film layer of the negative electrode plate.
[0163] In some embodiments, the dispersant may also include carboxymethyl cellulose salts.
[0164] In some embodiments, the ratio of the mass content of the carboxymethyl cellulose salt to the mass content of the polymer can be 0.5 to 2. When the mass content ratio of the carboxymethyl cellulose salt to the polymer is within the above range, it can work together with the polymer to improve the flexibility of the film formed by itself.
[0165] Illustratively, the ratio of the mass content of the carboxymethyl cellulose salt to the mass content of the polymer can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or a range consisting of any two of the above values.
[0166] Negative electrode
[0167] In the fourth aspect, the embodiment of the present application proposes a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a polymer as described in any embodiment of the first aspect of the present application or a polymer obtained by the preparation method described in any implementation of the second aspect of the present application. The polymer can be used as a dispersant in the negative electrode film layer, which can make the negative electrode active material evenly dispersed in the negative electrode film layer, so that the performance of the negative electrode film layer is uniform, and the dispersant can also improve the flexibility of the negative electrode film layer and reduce the risk of cracking of the negative electrode film layer. For example, the negative electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0168] In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the polymer is 0.8% to 1.3%, optionally 1.0% to 1.3%, and further optionally 1.0% to 1.2%. When the mass content of the polymer is within the above range, the performance uniformity and flexibility of the negative electrode film layer can be effectively improved, and its proportion is relatively low, which basically does not affect the proportion of the negative electrode active material, thereby making the battery monomer have a higher energy density. And because the polymer can significantly improve the flexibility of the negative electrode film layer, etc., it is not necessary to add additives such as plasticizers to the negative electrode slurry, thereby reducing the adverse effects caused by the introduction of plasticizers.
[0169] Illustratively, the mass content of the polymer can be 0.80%, 0.85%, 0.90%, 0.95%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.2%, 1.3% or a range consisting of any two of the above values.
[0170] In some embodiments, the negative electrode film layer may also include carboxymethyl cellulose salts, such as at least one of sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc. The difference between this type of carboxymethyl cellulose salt and the above-mentioned polymer is that the hydroxyl groups in this type of carboxymethyl cellulose salt are not replaced, and the carboxymethyl cellulose salt can play a dispersing role together with the above-mentioned polymer, and on this basis, the polymer can also additionally improve the flexibility of the negative electrode film layer.
[0171] In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the carboxymethyl cellulose salt can be 0.05% to 1.0%; optionally 0.05% to 0.3%. When the mass content of the carboxymethyl cellulose salt is within the above range, it can work together with the polymer to improve the performance uniformity and flexibility of the negative electrode film layer.
[0172] For example, the mass content of carboxymethyl cellulose salts can be 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.3%, 0.35%, 0.4%, 0.42%, 0.45%, 0.46%, 0.48%, 0.50%, 0.52%, 0.55%, 0.56%, 0.58%, 0.60%, 0.62%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 0.91%, 0.99%, 0.91%, 0.99%, 0.99%, 0 6%, 0.68%, 0.70%, 0.72%, 0.75%, 0.78%, 0.80%, 0.82%, 0.85%, 0.86%, 0.88%, 0.9%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00% or a range consisting of any two of the above values.
[0173] In some embodiments, the ratio of the mass content of the carboxymethyl cellulose salt to the mass content of the polymer can be 0.5 to 2. When the mass content ratio of the carboxymethyl cellulose salt to the polymer is within the above range, it can work together with the polymer to improve the performance uniformity and flexibility of the negative electrode film layer.
[0174] Illustratively, the ratio of the mass content of the carboxymethyl cellulose salt to the mass content of the polymer can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or a range consisting of any two of the above values.
[0175] In some embodiments, the coating weight of the negative electrode film layer is 190 mg / 1540.25 mm 2 Up to 230mg / 1540.25mm 2 ; Optional: 200mg / 1540.25mm 2 Up to 230mg / 1540.25mm 2 The coating weight of the negative electrode film layer is relatively high, which is conducive to achieving thick coating.
[0176] For example, the coating weight of the negative electrode film layer can be 190 mg / 1540.25 mm 2 , 200mg / 1540.25mm 2 , 210mg / 1540.25mm 2 , 220mg / 1540.25mm 2 、230mg / 1540.25mm 2 Or a range consisting of any two of the above values.
[0177] The negative electrode active material may be a negative electrode active material for a battery cell known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.
[0178] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The embodiment of the present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5%.
[0179] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5%.
[0180] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include thickeners, such as PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2%.
[0181] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0182] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, polymer, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0183] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the embodiments of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector. In some other embodiments, the negative electrode plate described in the embodiments of the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0184] Battery Cell
[0185] In a fifth aspect, the present application provides a battery cell, the battery cell comprising a negative electrode plate. The negative electrode plate comprises the negative electrode plate of any embodiment of the fourth aspect of the present application, and the use of the negative electrode plate can improve the dynamic performance of the battery cell.
[0186] [Positive electrode]
[0187] In some embodiments, the battery cell further includes a positive electrode tab.
[0188] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0189] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0190] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0191] In some embodiments, when the battery cell of the present application is a lithium-ion battery, the positive electrode active material may include but is not limited to at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of the lithium transition metal oxide may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate may include but are not limited to at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0192] The positive electrode film layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material may include at least one of the following materials: a layered structure positive electrode active material (such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium / sodium-rich layered and rock salt phase layered materials), an olivine-type phosphate active material, a spinel structured positive electrode active material (such as spinel lithium manganate, spinel nickel lithium manganate, lithium-rich spinel lithium manganate, and lithium nickel lithium manganate, etc.).
[0193] Exemplarily, the general formula of the layered positive electrode active material is: LixAyNiaCobMncM(1-abc)Yz, wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y is selected from one or more of O and F. Optionally, y=0. Specifically, the layered positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiN i 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co0 .2 Mn 0.3 O2 (NCM523) or more.
[0194] Exemplarily, the general formula of the olivine phosphate active material is: LixAyMeaMbP1-cXcYz, wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A is selected from one or more of Na, K, and Mg; Me is selected from one or more of Mn, Fe, Co, and Ni; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X is selected from one or more of S, Si, Cl, B, C, and N; Y is selected from one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO 4 , Li MnPO 4 , LiNiPO 4 , and LiCoPO 4 .
[0195] Exemplarily, the general formula of the positive electrode active material of the spinel structure is: LixAyMnaM2-aYz, wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y is selected from one or more of O and F. Specifically, the positive electrode active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.
[0196] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.
[0197] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, based on the total weight of the positive electrode film layer, the mass percentage of the binder is ≤5%.
[0198] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total weight of the positive electrode film layer, the mass percentage of the conductive agent is ≤5%.
[0199] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the optional conductive agent, the optional binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0200] [Electrolyte]
[0201] In some embodiments, the battery cell further includes an electrolyte.
[0202] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs.
[0203] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.
[0204] As an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0205] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0206] In some embodiments, the electrolyte may further include additives, for example, the additives may include positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0207] [Isolation film]
[0208] In some embodiments, the battery cell further includes a separator.
[0209] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0210] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0211] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0212] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0213] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0214] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0215] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0216] The preparation method of the battery cell of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0217] In some embodiments of the present application, the battery cells according to the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.
[0218] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0219] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0220] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0221] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0222] The battery according to the embodiment of the present application may include one battery cell or a plurality of battery cells. When the battery includes a plurality of battery cells, the battery may include a battery module or a battery pack.
[0223] Electrical devices
[0224] The sixth aspect of the embodiments of the present application provides an electric device, which includes at least one of the battery cells, battery modules or battery packs of the present application. The battery cells, battery modules or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0225] The electrical device may select a battery cell, a battery module or a battery pack according to its usage requirements.
[0226] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.
[0227] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0228] Example
[0229] The following embodiments describe the contents disclosed in the present application in more detail, and these embodiments are only used for illustrative explanations, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the present application disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0230] Preparation of Lithium Ion Batteries in Examples and Comparative Examples
[0231] 1. Preparation of positive electrode
[0232] Aluminum foil with a thickness of 13 μm was used as the positive electrode current collector.
[0233] The positive electrode active material lithium cobalt oxide LiCoO2, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are uniformly mixed in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 97.2:1.3:1.5 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.
[0234] 2. Preparation of negative electrode sheet
[0235] A copper foil with a thickness of 6 μm was used as the negative electrode current collector.
[0236] Artificial graphite as negative electrode active material, conductive carbon, adhesive styrene acrylic emulsion, and dispersant are mixed evenly in deionized water to prepare negative electrode slurry. The mass ratio of artificial graphite, conductive carbon, adhesive styrene acrylic emulsion, and dispersant in the solid components of the negative electrode slurry is 96.7:0.7:1.5:1.1. The negative electrode slurry is coated on the current collector copper foil and dried at 85°C and cold pressed to obtain a negative electrode sheet containing a negative electrode active material layer.
[0237] 3. Preparation of electrolyte
[0238] In an environment with a water content of less than 10 ppm, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then lithium salt lithium hexafluorophosphate and the mixed solvent are mixed, and the mass content of the lithium salt relative to the total mass of the electrolyte is 12.5%.
[0239] 4. Preparation of lithium-ion batteries
[0240] The positive electrode sheet, polyethylene PE separator (7 μm thickness), and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0241] Example 2-1 to Example 2-5
[0242] The difference from Example 1 is that the type of dispersant in the negative electrode slurry is different.
[0243] Example 3-1 to Example 3-4
[0244] The difference from Example 1 is that the amount of dispersant added to the negative electrode slurry is different.
[0245] In Example 3-1, the mass ratio of artificial graphite, conductive agent conductive carbon, binder styrene acrylic emulsion, and dispersant modified CMC-Na in the solid components of the negative electrode slurry is 96.8:0.7:1.5:1.0.
[0246] In Example 3-2, the mass ratio of artificial graphite, conductive agent conductive carbon, binder styrene acrylic emulsion, and dispersant modified CMC-Na in the solid components of the negative electrode slurry is 96.6:0.7:1.5:1.2.
[0247] In Example 3-3, the mass ratio of artificial graphite, conductive agent conductive carbon, binder styrene acrylic emulsion, and dispersant modified CMC-Na in the solid components of the negative electrode slurry is 96.5:0.7:1.5:1.3.
[0248] In Example 3-4, the mass ratio of artificial graphite, conductive agent conductive carbon, binder styrene acrylic emulsion, dispersant modified CMC-Na, and CMC-Na in the solid components of the negative electrode slurry is 96.7:0.7:1.5:0.8:0.3.
[0249] Example 4-1 to Example 4-4
[0250] Different from Example 1, the molecular weight of the dispersant in the negative electrode slurry is different.
[0251] Example 5-1 to Example 5-2
[0252] The difference from Example 1 is that the cations of the dispersant in the negative electrode slurry are different.
[0253] Example 6-1 to Example 6-2
[0254] Different from Example 1, the grafting group of the dispersant in the negative electrode slurry is different;
[0255] In Example 6-1, the modified CMC-Na includes a copolymerized first repeating unit and a second repeating unit, the first repeating unit is formed by grafting modification of CMC by formula (1-1), and the degree of polymerization of the first repeating unit is 35, the second repeating unit is formed by grafting modification of CMC by formula (2-1), and the degree of polymerization of the second repeating unit is 35, the degree of polymerization of the modified CMC-Na can be considered to be the sum of the two repeating units, and the degree of polymerization of the modified CMC-Na is 70.
[0256] In Example 6-2, the modified CMC-Na includes a first repeating unit and a second repeating unit of copolymerization. The first repeating unit is formed by grafting modification of CMC by formula (1-1), and the degree of polymerization of the first repeating unit is 35. The second repeating unit is formed by grafting modification of CMC by formula (1-10), and the degree of polymerization of the second repeating unit is 35. The degree of polymerization of the modified CMC-Na can be considered to be the sum of the two repeating units, and the degree of polymerization of the modified CMC-Na is 70.
[0257] Comparative Example 1
[0258] Different from Example 1, a dispersant is added to the negative electrode slurry, and the dispersant is replaced by sodium carboxymethyl cellulose. The mass ratio of artificial graphite, conductive carbon, adhesive styrene acrylic emulsion, and dispersant CMC-Na in the solid components of the negative electrode slurry is 96.7:0.7:1.5:1.1.
[0259] Comparative Example 2
[0260] Different from Example 1, a dispersant is added to the negative electrode slurry, the dispersant is replaced by sodium carboxymethyl cellulose, and a plasticizer is added to the negative electrode slurry, and the mass ratio of artificial graphite, conductive carbon, adhesive styrene acrylic emulsion, dispersant CMC-Na, and plasticizer butanediol in the solid components of the negative electrode slurry is 96.55:0.7:1.5:1.1:0.15.
[0261] The relevant parameters of the embodiments and comparative examples are shown in Table 1.
[0262] Test Section
[0263] 1. Negative electrode slurry filterability test:
[0264] The filter screen is 150 mesh and is cut into 25cm*25cm pieces with scissors.
[0265] Fold a 150-mesh filter into a fan shape and hang it above the mouth of a clean beaker. Pour 500 mL of negative electrode slurry into the filter at once. When the negative electrode slurry starts to flow out from the tip of the filter, start recording the time. Record the filtration time for 300 mL.
[0266] 2. Gel and sedimentation state of negative electrode slurry:
[0267] Take 500 ml of negative electrode slurry, leave it for different periods of time to observe whether it appears in a jelly gel state, and test its slurry viscosity. If the viscosity of the upper slurry in the test beaker decreases and the lower slurry becomes thicker, it means that slurry sedimentation occurs.
[0268] 3. Coating weight of negative electrode film layer:
[0269] The coating window measures the approximate critical range of the quality stability of the coated product. Exceeding this range will lead to defects such as cracking. The coating is carried out using an extrusion coater at a speed of 50 m / min. As the coating quality of the negative electrode sheets of the comparative examples and the embodiments gradually improves, observe whether the film layer has cracks. If there are no cracks, continue to increase the weight until the film layer on the surface of the sheet cracks. Record the coating weight that the negative electrode film layer can bear without cracking, which is the coating weight of the negative electrode film layer in Table 1.
[0270] 4. DC impedance test of lithium-ion battery
[0271] The battery DC impedance test process is as follows: at 25°C, the lithium ion batteries prepared in the examples and comparative examples are charged to 4.2V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage of 4.2V, and after standing for 5 minutes, the voltage V1 is recorded. Then, the battery is discharged at 1 / 3C for 30 seconds, and the voltage V2 is recorded. Then, (V2-V1) / (1 / 3C) is used to obtain the internal resistance DCR of the lithium ion battery.
[0272] Test Results
[0273] The test results are shown in Table 1
[0274] Table 1
[0275]
[0276]
[0277] According to the gel and sedimentation tests of the above embodiments and comparative examples, the negative electrode slurry has no sedimentation and no gel, and the state of the negative electrode slurry is relatively stable.
[0278] As can be seen from Table 1, in Comparative Example 1, a dispersant sodium carboxymethyl cellulose CMC-Na is added to the negative electrode slurry. The sodium carboxymethyl cellulose has not been modified by the side chain, which is beneficial to improving the dispersion performance of the negative electrode active material in the negative electrode slurry. However, due to the hydrogen bonding effect of the sodium carboxymethyl cellulose itself, it is not conducive to thick coating of the negative electrode slurry. The coating weight is small, and in the process of drying the negative electrode slurry into a negative electrode film layer, it is easy to cause the negative electrode film layer to crack and other problems.
[0279] Compared with Comparative Example 1, Comparative Example 2 also adds a plasticizer to the negative electrode slurry. The plasticizer can effectively improve the shaping ability and flexibility of the negative electrode film layer, which is beneficial to the thick coating of the negative electrode slurry. The coating weight is improved and the cracking phenomenon of the negative electrode film layer can be improved. However, after testing, it was found that the thickness of the negative electrode film layer with the addition of plasticizer was uneven and the impedance of the negative electrode film layer was high.
[0280] However, in the embodiment of the present application, no plasticizer is added to the negative electrode slurry. In order to improve the performance uniformity of the negative electrode film layer, the dispersant sodium carboxymethyl cellulose is modified by side chain grafting, which can reduce the hydrogen bonding effect of the dispersant, improve the performance of the negative electrode film layer, and reduce the occurrence of cracking of the negative electrode film layer. It can also further reduce the impedance of the negative electrode film layer and improve the dynamic performance of the lithium-ion battery. Example 1, Example 3-1 to Example 3-4 regulate the amount of dispersant added in the negative electrode slurry, which can effectively adjust the thickness of the negative electrode slurry, improve the flexibility of the negative electrode film layer, and reduce the impedance of the negative electrode film layer.
[0281] The dispersants of Examples 3-4 include two types, one is the polymer of the present application (modified sodium carboxymethyl cellulose), and the other is sodium carboxymethyl cellulose. Compared with Examples 3-4, the amount of dispersant added in Example 1 is the same as that in Example 3-4, but the coating performance of Example 1 and the performance of the lithium-ion battery are significantly further improved.
[0282] The present application performs multiple tests on the negative electrode plate in Example 1. For example, ion polishing cross-sectional element analysis (CP) is performed at 10 locations of the negative electrode plate in accordance with GB / T17359-2012 to confirm the thickness of the negative electrode film layer in the negative electrode plate. The thickness deviation of the negative electrode film layer obtained from the 10 tests is controlled within the range of 0.5%. It can be considered that the thickness of the negative electrode film layer in the negative electrode plate is uniform and the thickness consistency is high.
[0283] In the present application, 10 lithium-ion batteries are prepared by the method described in Example 1, and the average thickness of the negative electrode film layer of each lithium-ion battery is measured, that is, ion polishing cross-sectional element analysis (CP) is performed with reference to GB / T 17359-2012, the thickness of the negative electrode film layer at 10 locations in the negative electrode sheet is measured, and the average value is calculated as the average thickness of the lithium-ion battery. The thickness deviation of the negative electrode film layer of the 10 lithium-ion batteries is controlled within a range of 0.5%.
[0284] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A polymer comprising modified carboxymethyl cellulose salts, wherein the modified carboxymethyl cellulose salts are carboxymethyl cellulose salts in which at least one hydrogen atom of a hydroxyl group is substituted with a grafted group; the grafted group comprises at least one of a polyether group and a substituted or unsubstituted polyalkyl group.
2. The polymer according to claim 1, wherein the modified carboxymethyl cellulose salt comprises at least one of modified carboxymethyl cellulose lithium salt, modified carboxymethyl cellulose sodium salt or modified carboxymethyl cellulose ammonium salt.
3. The polymer according to claim 1 or 2, wherein the modified carboxymethyl cellulose salt comprises a compound represented by formula (A), In formula (A), M includes Li, Na or NH 4 At least one of; R 1 To R 5 Each independently includes at least one of a hydrogen atom, a C5 to C150 polyether group, a substituted or unsubstituted C5 to C150 saturated alkyl group, and a substituted or unsubstituted C5 to C150 polyalkenyl group, and R 1 To R 5 At least one of the following comprises at least one of a C5 to C150 polyether group, a substituted or unsubstituted C5 to C150 saturated alkyl group, and a substituted or unsubstituted C5 to C150 polyalkenyl group, in, The grafted group includes R 1 To R 5 The non-hydrogen atom groups in n represents the degree of polymerization of the modified carboxymethyl cellulose salt; optionally, n includes any positive integer from 1500 to 3000.
4. The polymer according to any one of claims 1 to 3, in, The grafted group includes a polyether group, and the polyether group includes the structural formula shown in formula (1), In formula (1), R 11 To R 17 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, a substituted or unsubstituted C1 to C10 alkenyl group, and a substituted or unsubstituted C1 to C10 alkynyl group; m includes any positive integer from 5 to 60.
5. The polymer according to any one of claims 1 to 4, in, The grafted group includes at least one of the structural formulas shown in formula (1-1) to formula (1-14), 6. The polymer according to any one of claims 1 to 5, in, The grafted group includes a substituted or unsubstituted first group, and the substituted or unsubstituted first group includes the structural formula shown in formula (2), In formula (2), R 21 To R 27 Each independently includes at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group; s includes any positive integer from 5 to 60.
7. The polymer according to any one of claims 1 to 6, in, The grafted group includes at least one of the structural formulas shown in formula (2-1) to formula (2-10), 8. The polymer according to any one of claims 1 to 7, in, The grafted group includes a substituted or unsubstituted second group, and the substituted or unsubstituted second group includes the structural formula shown in formula (3), In formula (3), R 31 To R 34 Each independently includes at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C10 alkyl group, and a substituted or unsubstituted C1 to C10 alkenyl group; R 35 including at least one of a hydrogen atom, a halogen atom, and a substituted or unsubstituted C1 to C10 alkyl group; p includes any positive integer from 5 to 60.
9. The polymer according to any one of claims 1 to 8, in, The grafted group includes at least one of the structural formulas shown in formula (3-1) to formula (3-8), 10. The polymer according to any one of claims 1 to 9, in, The weight average molecular weight of the grafted group is 100Da to 5000Da.
11. The polymer according to any one of claims 1 to 10, in, The weight average molecular weight of the polymer is 40 wDa to 80 wDa.
12. The polymer according to any one of claims 1 to 11, in, The breaking elongation of the reference film made of sodium carboxymethyl cellulose is 100%, and the breaking elongation of the film made of the polymer is 170% to 300%. The width of the polymer film and the reference film is 2.5 cm, the length is 5 cm, and the thickness is 1 mm. 13 . A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises the polymer according to any one of claims 1 to 12.
14. The negative electrode sheet according to claim 13, in, Based on the total mass of the negative electrode film layer, the mass content of the polymer is 1.0% to 1.3%, and optionally 1.0% to 1.2%.
15. The negative electrode sheet according to claim 13 or 14, in, The coating weight of the negative electrode film layer is 190 mg / 1540.25 mm 2 Up to 230mg / 1540.25mm 2 ; Optional: 200mg / 1540.25mm 2 Up to 230mg / 1540.25mm 2 .
16. A battery comprising the negative electrode sheet according to any one of claims 13 to 15.
17. An electrical device comprising the battery as claimed in claim 16.
Citation Information
Patent Citations
Adhesive for lithium ion battery
CN105504169A
Synthesis method of carboxymethyl-hydroxyethyl cellulose salt
CN111349180A
Negative plate and lithium ion battery comprising same
CN111900357A
method for OBTAINING SODIUM SALT OF CARBOXYMETHYLCELLULOSE
RU2005119672A
